Sintesis dan Karakterisasi Komposit Selulosa Bakteri dengan Grafit dan TiO2-ZnO: Structural and Functional Analysis - Fariz Nafiir, Muhammad; Sudirman; Yuanita, Emmy; Arshad, Sazmal E.; Lusiana, Retno Ariadi; Ulfa, Maria (Acta Chimica Asiana, 2024)
This research aims to synthesize and characterize a bacterial cellulose (BC)-based composite with graphite and TiO2-ZnO as reinforcement materials using ex-situ synthesis with CTAB as a surfactant. FTIR and SEM-EDS analysis revealed interactions between the matrix and the reinforcement materials, as well as irregular particle distribution in the BC/G-TiO2-ZnO composite. The addition of graphite to BC significantly increased the conductivity of the composite, while the addition of TiO2-ZnO had the opposite effect. The mechanical properties of the composite exhibited an inverse relationship with the conductivity parameter. Swelling tests indicated that pH and the addition of CTAB influenced the swelling behavior of the BC-based composite. The results of this study provide a strong foundation for the development of potential applications in the fields of electronics and pollutant filtration. The synthesis of this composite aims to harness the unique properties of BC, graphite, and TiO2-ZnO, creating a multifunctional material with potential uses in flexible electronics, sensors, biocompatible conductive materials, and advanced filtration systems.